Bilateral, symmetrical, tripartite variation of the anterior belly of digastric muscle - Thérèse F. Weidenkopf; Jialin Chen; Kelly M. Harrell (Elsevier, 2024)
Background: The anterior and posterior bellies of digastric muscle act to facilitate components of phonation, jaw opening, and hyoid bone stabilization during swallowing. Variations in the digastric muscle within the submental triangle are well-documented in the literature. Ongoing and up-to-date reporting and knowledge of these variations is important from a clinical perspective. Method: Routine human anatomical dissection of the anterior neck in a male donor revealed bilateral pairs of accessory muscles (n = 4) attached to and within the depth plane of right and left anterior bellies of digastric muscles. Results: The case presented here is of a bilateral, tripartite digastric muscle variation within the submental triangle of an anatomical donor. Attachments and relationships were noted. Variant digastric muscles were found to be innervated by the nerve to the mylohyoid muscle and supplied by the submental artery, consistent with supply to the anterior belly of the digastric muscle. Conclusion: The clinical relevance of these additional muscles primarily pertains to radiological evaluation and reconstructive surgical procedures in the submental region, as digastric muscle bellies serve as essential landmarks and potential targets. Describing anatomical variations is crucial for appropriate planning of interventions in this region.